A revision of the subfamily Araeopteroninae Fibiger, 2005 in the Russian Far East and neighbouring countries with a description of four new species (Lepidoptera, Noctuidae) - Fibiger, Michael; Kononenko, Vladimir (Zootaxa, 2008)
The subfamily Araeopteroninae Fibiger, 2005 from the Russian Far East and neighbouring countries is revised. Six species occur in Russia, three of which are new: A. ussurica sp. n., A. makikoae sp. n. and A. patella sp. n.; A. fragmenta and A. nebulosa are reported for the first time for Russia. In South Korea five species occur, two of which are new: A. patella sp. n. and A. koreana sp. n. Three species, A. amoena, A. nebulosa, and A. fragmenta are reported for the first time from China. The formerly described Far Eastern species (A. amoena, A. nebulosa, A. fragmenta and A. flaccida) are redescribed based on morphological characters. Adultss of all species from northern East Asia treated in the article are illustrated in color with their male and female genitalia. Distribution maps of the species in the Russian Far East are presented, along with an alphabetic checklist of 36 described species.